2018
DOI: 10.5958/0976-5506.2018.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Regressions of a Malcolm Baldrige's Patient Safety Models

Abstract: This research proposed to develop patient safety models in primary health care and provide a possible model to implementated. Primary health care in Indonesia battling in assessment of risk reduction strategy because difficulty in identifying adverse event and there are no model or guidance for patient safety in primary health care yet. The patient safety model can be framed with Baldrige Health Care Criteria for performance excellence. Basic Emergency Obstetric Care was an critical health care in Indonesia fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 10 publications
6
3
1
Order By: Relevance
“…The results showed that the correlation detection and patient safety incidents. This study is in line with research which states there is a significant relationship between incident detection with patient safety [29]. Incident detection efforts made by an early vote on matters that may pose a danger to the safety of patients.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The results showed that the correlation detection and patient safety incidents. This study is in line with research which states there is a significant relationship between incident detection with patient safety [29]. Incident detection efforts made by an early vote on matters that may pose a danger to the safety of patients.…”
Section: Discussionsupporting
confidence: 89%
“…This is seen often establish effective communication between the heads of primary health care with staff and fellow staff at the primary health care Basic Emergency Neonatal Obstetric Services, often there is a learning and development in the primary health care staff on a regular basis and there is a change of behavior Basic Emergency Neonatal Obstetric Services patient safety after learning. From the bivariate analysis shows that there are relationship mitigation and safety of patients, this study is in line with research which states there is a significant relationship between mitigation with patient safety [29]. One form of mitigation is to establish effective communication between the heads of primary health care with staff and fellow staff at the primary health care Basic Emergency Neonatal Obstetric Services, As Parker [2015) states the communication within the team is very important and affect the safety of patients, with effective communication will reduce the risk of errors in the work [34].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations